Origin of Pressure‐Induced Metallization in Cu3N: An X‐ray Absorption Spectroscopy Study (Phys. Status Solidi B 11/2018). Issue 11 (15th November 2018) - Kuzmin, Alexei; Anspoks, Andris; Kalinko, Aleksandr; Timoshenko, Janis; Nataf, Lucie; Baudelet, François; Irifune, Tetsuo
Abstract : X‐ray absorption spectroscopy is a powerful tool to probe in situ changes in the local structure of a material induced by pressure. In article no.1800073 it was used by Kuzmin et al. to study the behavior of copper nitride (Cu3 N) crystal lattice at high pressure (0–26.7 GPa). The analysis of the Cu K‐edge X‐ray absorption near‐edge structure (XANES) and extended X‐ray absorption fine structure (EXAFS) suggests that at all pressures the local atomic environment around copper atoms remains close to that in cubic Pm‐3m phase. At the same time, a reduction of the lattice parameter of Cu3 N by about 2% was found upon increasing pressure up to 26.7 GPa. These results indicate that the transition to the metal state in Cu3 N above 5 GPa, observed previously using pressure‐dependent electrical resistance and optical absorption measurements, is due to the band gap collapse with a decrease of the unit cell volume.